AN ANALYSIS OF FACTORS AFFECTING STUDENTS PRONUNCIATION AT 8TH GRADE OF SMP N 4 GUNUNG TALANG - Sherly Sri Arsifa; Merry Prima Dewi; Eliza; Absharini Kardena (Fakultas Tarbiyah Institut Agama Islam Ngawi, 2024)
This study was conducted to find out whether pronunciation is the most important problem in students' speaking and what factors affect students' pronunciation the most. This research has been completed at SMP N 4 Gunung Talang. This research was conducted because students pronounce sentences according to what is written, students do not pay attention to the teacher when learning takes place, and students feel embarrassed when pronouncing sentences in English. This research is a quantitative research with purposive sampling method with a sample size of 30 people. To collect research data, researcher used documents and questionnaires. In analyzing the data, the researcher analyzed the results of the assessment of the four aspects of student speaking and calculating mean score, for the research questionnaire was calculated using the percentage formula and Likert scale formula. From the results of the analysis of the four aspects of speaking namely pronunciation, grammar, vocabulary and fluency it was found that, pronunciation aspect was the lowest score. And from the results of the questionnaire analysis it was found that native language was the dominant factor that most influenced students' pronunciation. The findings of this study contain two findings, the first is that pronunciation is the main problem in students' speaking assessment, and identity and language ego is the factor that most affects students' pronunciation with percentage 79, 96%.